1995
DOI: 10.1080/10473289.1995.10467411
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Organic Acids, Aldehydes, and Ketones in Residential Environments and Their Relation to Ozone

Abstract: Ozone and several polar volatile organic compounds (VOCs) including organic acids and carbonyls (aldehydes and ketones) were measured over an approximately 24 hour period in four residences during the winter of 1993 and in nine residences during the summer of 1993. All residences were in the greater Boston, Massachusetts area. The relation of the polar VOCs to the ozone concentration was examined. Indoor carbonyl concentrations were similar between the summer and winter, with the total mean winter concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 23 publications
3
54
1
Order By: Relevance
“…Hodgson et al (2000) found that in new homes, formaldehyde and odorous aldehydes, especially hexanaldehyde, were among the most prevalent and predominant VOCs. The same tendency was seen in measurements done in Boston (Reiss et al, 1995a).…”
Section: Comparisons Between Locations Considering Sourcessupporting
confidence: 68%
See 2 more Smart Citations
“…Hodgson et al (2000) found that in new homes, formaldehyde and odorous aldehydes, especially hexanaldehyde, were among the most prevalent and predominant VOCs. The same tendency was seen in measurements done in Boston (Reiss et al, 1995a).…”
Section: Comparisons Between Locations Considering Sourcessupporting
confidence: 68%
“…Similarly, Weschler et al (1992) found that in a laboratory study ozone reacted with carpet to form aldehydes. Aldehydes emission rates in indoor environments measured in Boston (MA, USA), where ambient ozone concentrations are lower than in Mexico City, were found to be correlated with temperature, relative humidity and ozone removal rate (Reiss et al, 1995a). During an indoor-outdoor aldehyde study, Zhang et al (1994) also found that acetaldehyde and isovaleraldehyde were significantly correlated with ozone.…”
Section: Factor Analysismentioning
confidence: 76%
See 1 more Smart Citation
“…Some of the compounds of concern are ethanolamine, laural dimethyl benzyl ammonium chloride, benzalkonium chloride, formaldehyde and other carbonyls, toluene, 4-nonylphenol, and glycol ethers such as 2-butoxy ethanol, 2-(2-ethoxyethoxy)ethanol, and 2-(2-butoxyethoxy)ethanol (reviewed in Nazaroff and Weschler, 2004). In addition, ambient ozone enters homes from the outdoors (Weschler et al, 1992;Reiss et al, 1995;Weschler, 2000) and reacts with unsaturated compounds in cleaning products forming secondary pollutants of concern (Weschler, 2006). There are a number of unsaturated terpenes found in cleaning products, such as a-pinine, used for its pine scent, and d-limonene, used for its lemon scent, as well as other terpene-related compounds, such as a-terpineol, linalool, and linalyl acetate.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the emissions of formic and acetic acids from latex paints have been reported to increase dramatically with relative humidity; for example, for one paint sample the emission rate for acetic acid almost tripled when the relative humidity was changed from 4-5% to 5-23% (Reiss et al, 1995b). A number of different aldehydes have been measured indoors (Crump & Gardiner, 1989;Lewis & Zweidinger, 1992;Zhang et al, 1994;Daisey et al, 1994;and Reiss et al, 1995a), some of which are directly emitted and some of which are formed by chemical reactions indoors of VOCs such as styrene. Of these, there is an enormous amount of evidence for direct emissions of HCHO from building materials.…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%